2016
DOI: 10.1002/2015wr017525
|View full text |Cite
|
Sign up to set email alerts
|

Debates—Stochastic subsurface hydrology from theory to practice: The relevance of stochastic subsurface hydrology to practical problems of contaminant transport and remediation. What is characterization and stochastic theory good for?

Abstract: The emergence of stochastic subsurface hydrology stemmed from the realization that the random spatial variability of aquifer properties has a profound impact on solute transport. The last four decades witnessed a tremendous expansion of the discipline, many fundamental processes and principal mechanisms being identified. However, the research findings have not impacted significantly the application in practice, for several reasons which are discussed. The paper discusses the current status of stochastic subsur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 36 publications
2
42
0
1
Order By: Relevance
“…Stochastic methods have been developed by hydrologists to describe solute transport in heterogeneous media for approximately 40 years, but these models usually exhibit poor predictability and lack hydrogeologic information; see extensive discussion by Cirpka and Valocchi (); Fiori et al (); Fogg and Zhang (); Rajaram (); and Sanchez‐Vila and Fernandez‐Garcia (). Our study found that the time nonlocal transport model (with constant parameters), as a popular stochastic model, might be challenged further by scale‐dependent dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Stochastic methods have been developed by hydrologists to describe solute transport in heterogeneous media for approximately 40 years, but these models usually exhibit poor predictability and lack hydrogeologic information; see extensive discussion by Cirpka and Valocchi (); Fiori et al (); Fogg and Zhang (); Rajaram (); and Sanchez‐Vila and Fernandez‐Garcia (). Our study found that the time nonlocal transport model (with constant parameters), as a popular stochastic model, might be challenged further by scale‐dependent dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…At the Basel site, the subsurface uncertainty strongly influences the flow gradients and spreading of the pathlines as reflected in the pathline density distributions. This finding can have significant implications for field work and water management strategies (McKenna and Wahi 2006; Devlin and Schillig 2017) as well as for transport of pollutants in the subsurface (Fiori et al 2016;Frind and Molson 2018). The NSMC analysis can be combined with various models and model predictions (e.g., Tonkin and Doherty 2009;Moeck et al 2018) and does not necessarily include PT as applied in this study.…”
Section: Nsmc Analysis With Pilot Point Approachmentioning
confidence: 99%
“…A recent debates series (Rajaram, 2016;Fiori et al, 2016;Fogg and Zhang, 2016;Cirpka and Valocchi, 2016;Sanchez-Vila and Fernàndez-Garcia, 2016) outlined the gap between the advanced research in stochastic subsurface hydrology and its application in the practice of groundwater flow and transport modeling. We see a significant reason in the lack of data for complex stochastic models.…”
Section: Introductionmentioning
confidence: 99%